2017
DOI: 10.15448/1980-6108.2017.4.28050
|View full text |Cite
|
Sign up to set email alerts
|

Respiração lenta e profunda aumenta a modulação vagal em gestantes

Abstract: Este artigo está licenciado sob forma de uma licença Creative Commons Atribuição 4.0 Internacional, que permite uso irrestrito, distribuição e reprodução em qualquer meio, desde que a publicação original seja corretamente citada. RESUMOOBJETIVOS: Comparar a resposta da modulação autonômica da frequência cardíaca de gestantes e mulheres não gestantes, antes e após a manobra de acentuação da arritmia sinusal respiratória. MÉTODOS: Foi realizado um estudo transversal com amostra de 24 mulheres, divididas em dois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 21 publications
0
0
0
1
Order By: Relevance
“…About the root mean square of successive differences (RMSSD) and the standard deviation of the RR interval (SDRR), that represents the total HRV, significant differences were found between pregnant and nonpregnant women in the articles by Carpenter et al 14 and Farche et al, 15 this last one did not assess the SDRR, only frequency domains variables and RMSSD, in all assessed moments. Regarding pregnant women who practiced and did not practice physical exercise, Carpenter et al 14 found statistically significant difference in only pregnant women at 34-36 gestational weeks, in the mentioned indices, similar to May et al, 16 that found differences in pregnant women at 28 and 36 gestational weeks.…”
Section: Time Domain Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…About the root mean square of successive differences (RMSSD) and the standard deviation of the RR interval (SDRR), that represents the total HRV, significant differences were found between pregnant and nonpregnant women in the articles by Carpenter et al 14 and Farche et al, 15 this last one did not assess the SDRR, only frequency domains variables and RMSSD, in all assessed moments. Regarding pregnant women who practiced and did not practice physical exercise, Carpenter et al 14 found statistically significant difference in only pregnant women at 34-36 gestational weeks, in the mentioned indices, similar to May et al, 16 that found differences in pregnant women at 28 and 36 gestational weeks.…”
Section: Time Domain Analysismentioning
confidence: 99%
“…Twelve studies were included in this review, which five were nonrandomized clinical trials, [13][14][15][16][17] four, randomized clinical trials, [18][19][20][21] and three, cross-sectional studies. [22][23][24] 20 also evaluated overweight participants.…”
Section: Characterization Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…O conhecimento da entropia vem sendo utilizado em diversas áreas do conhecimento, como na medicina (FARCHE et al, 2017), na ecologia (JULES, 2017), biologia (FERNANDES et al, 2003), climatologia (CHEN, 2008), dentre outras. Para o cálculo da entropia foi utilizada a equação proposta por Shannon (1948) (Eq.…”
Section: Analysis Of the Entropy Theory Using Pluviometric Data In The State Of Paraíbaunclassified